Effect of Adenotonsillectomy on Peak Expiratory Flow Rate Among Children - Singhal, Akshi; Kumar, Lovneesh; Agarwal, Vinish Kumar; Bist, Sampan Singh; Agrawal, Nitika (Indian journal of otolaryngology, and head, and neck surgery, 2022)
Adenotonsillar hypertrophy is one of the commonest causes of upper airway obstruction in children. It can cause hypoxic state by impairing pulmonary functions. Peak expiratory flow rate is a basic, convenient and reliable indicator of pulmonary function in children. To study the improvement in pulmonary functions by assessing Peak expiratory flow rate, before and after adenotonsillectomy in children. Design: Cross sectional, prospective, observational study. Setting: Department of otorhinolaryngology in tertiary care centre. Subjects: Included 40 children aged between 5 and 15 years, who had adenotonsillar hypertrophy and underwent adenotonsillectomy. Method: Diagnostic nasal endoscopy and X-ray, nasopharynx, was done to assess the grade of adenoid hypertrophy endoscopically and radiologically respectively. Peak expiratory flow rate was assessed using Mini Wright peak expiratory flow meter pre-operatively and 1 month post-operatively and both the readings were compared. Subjective improvement was also compared pre-operatively and post-operatively using visual analogue score. This study included 40 patients with male to female ratio of 1.6:1, 92.5% presented with mouth breathing. 92.5% presented with grade III tonsillar hypertrophy and 70% with grade III adenoid hypertrophy endoscopically. After adenotonsillectomy, improvement in Peak expiratory flow rate ranged from 16 to 25.3% which was statistically significant. Patients with grade III tonsillar and grade IV adenoid hypertrophy showed 25.3% improvement. Subjective improvement was 98.8% in the complaint of snoring. Adenotonsillectomy significantly improves pulmonary functions. This may help to improve physical and cognitive development in children and decrease chances of getting cardiopulmonary problems in later life.